Enhancing the work placement experience of students with disabilities. Issue 6 (December 2022) - Mogaji, Emmanuel; Nguyen, Nguyen P
Work placement learning enhances self-efficacy and work readiness for students. However, students with disabilities often have a different experience with regard to work placements. With a growing number of people with disabilities in universities, it is essential to provide students who have disabilities with an inclusive learning and working environment. Expanding on previous studies that have explored industrial work placement in higher education across different levels of disabilities, this study is contextualised in Nigeria and adopts an integrative literature review approach to critically review and synthesise the literature on student experience, disability, work placement and higher education in the country. This process enables the development of a new theoretical framework and perspective for enhancing the work placement experience of students with disabilities. The study contributes to the existing knowledge regarding work experience, students with disabilities and student experiences in developing countries. It also has practical implications for stakeholders involved in work placements for students with disabilities.